Evaluasi Program Manajerial Kepala Sekolah - Virgo, Egidius; Slameto, Slameto (Kelola: Jurnal Manajemen Pendidikan, 2018)
The aim of this study is to evaluate the context, input, process, and product of the Principal Managerial Program in a Salatiga Private Elementary School. This study is evaluative research using CIPP models. The data collection includes interviews, documentation studies, and observations. The data validation was technique and resource triangulation. The study results: a) the context evaluation showed the managerial program of principals in private elementary schools is indeed very much needed by school stakeholders; b) the input evaluation showed the principal managerial program has been prepared to meet stakeholder needs, but has not been supported by human resources, funding, and adequate infrastructure; c) the process evaluation showed the principal’s managerial program carried out based on management functions namely: planning, organizing, supervision, and assessment. Even though it is constrained in terms of human resources, funding, and infrastructure, but the principal still can carry out a minimum managerial program, d) the product evaluation showed the Private Elementary School achieves more in the non-academic field than in the academic field, although from year to year there is a slight increase in the quality of student learning outcomes.